Lipoprotein(a) as a cardiovascular risk factor: current status - Nordestgaard, Børge G. (Oxford University Press, 2010)
AIMS: The aims of the study were, first, to critically evaluate lipoprotein(a) [Lp(a)] as a cardiovascular risk factor and, second, to advise on screening for elevated plasma Lp(a), on desirable levels, and on therapeutic strategies. METHODS AND RESULTS: The robust and specific association between elevated Lp(a) levels and increased cardiovascular disease (CVD)/coronary heart disease (CHD) risk, together with recent genetic findings, indicates that elevated Lp(a), like elevated LDL-cholesterol, is causally related to premature CVD/CHD. The association is continuous without a threshold or dependence on LDL- or non-HDL-cholesterol levels. Mechanistically, elevated Lp(a) levels may either induce a prothrombotic/anti-fibrinolytic effect as apolipoprotein(a) resembles both plasminogen and plasmin but has no fibrinolytic activity, or may accelerate atherosclerosis because, like LDL, the Lp(a) particle is cholesterol-rich, or both. We advise that Lp(a) be measured once, using an isoform-insensitive assay, in subjects at intermediate or high CVD/CHD risk with premature CVD, familial hypercholesterolaemia, a family history of premature CVD and/or elevated Lp(a), recurrent CVD despite statin treatment, ≥3% 10-year risk of fatal CVD according to European guidelines, and/or ≥10% 10-year risk of fatal + non-fatal CHD according to US guidelines. As a secondary priority after LDL-cholesterol reduction, we recommend a desirable level for Lp(a) <80th percentile (less than ∼50 mg/dL). Treatment should primarily be niacin 1–3 g/day, as a meta-analysis of randomized, controlled intervention trials demonstrates reduced CVD by niacin treatment. In extreme cases, LDL-apheresis is efficacious in removing Lp(a). CONCLUSION: We recommend screening for elevated Lp(a) in those at intermediate or high CVD/CHD risk, a desirable level <50 mg/dL as a function of global cardiovascular risk, and use of niacin for Lp(a) and CVD/CHD risk reduction.